Review of Law Enforcement in Indonesia - Munawar, Sepa (Lembaga Yasin AlSys, 2023)
Law enforcement is the process of making efforts to enforce or function legal norms in a real way as a guide for behavior in traffic or legal relations in social and state life. The problem of law enforcement in society is very urgent. Considering the existence of the law itself cannot be separated from social and state life. The purpose of this study is to find out what law enforcement is, the importance of law enforcement, the low level of law enforcement in Indonesia and the various factors that surround it. The method that the author uses is a type of normative legal research (Normative Legal Research), which is